Medical aspects of developmental disabilities in children birth to trree - Blackman, James A. (Washington: Aspen Plublishers, 1984)
The health status of disabled chilcren has a profound effect on their development. It is therefore essential that early intervention professionals in the educational setting are knowledgeable about the health and functionigof the children they serve. Without such knowledge, educators may be untions or treatments can place on a child' s progress.
Keywords: Pediatrician, Infant